Prevention of Clostridium difficile Infection: A Systematic Survey of Clinical Practice Guidelines. (7th June 2016) - Lytvyn, Lyubov; Mertz, Dominik; Sadeghirad, Behnam; Alaklobi, Faisal; Selva, Anna; Alonso-Coello, Pablo; Johnston, Bradley C.
Abstract : BACKGROUND: Clostridium difficile infection (CDI) is the most common cause of hospital-acquired infectious diarrhea. OBJECTIVE: To analyze the methodological quality, content, and supporting evidence among clinical practice guidelines (CPGs) on CDI prevention. DESIGN AND SETTING: We searched medical databases and gray literature for CPGs on CDI prevention published January 2004-January 2015. Three reviewers independently screened articles and rated CPG quality using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument, composed of 23 items, rated 1–7, within 6 domains. We reported each domain score as a percentage of its maximum possible score and standardized range. We summarized recommendations, extracted their supporting articles, and rated individually the level of evidence using the Oxford Centre for Evidence-Based Medicine Levels of Evidence. RESULTS: Of 2, 578 articles screened, 5 guidelines met inclusion criteria. Median AGREE II scores and interquartile ranges were: clarity of presentation, 75.9% (75.9%–79.6%); scope and purpose, 74.1% (68.5%–85.2%); editorial independence, 63.9% (47.2%–66.7%); applicability, 43.1% (19.4%–55.6%); stakeholder involvement, 40.7% (38.9%–44.4%); and rigor of development, 18.1% (17.4%–35.4%). CPGs addressed several common strategies for CDI prevention, including antibiotic stewardship, hypochlorite solutions, probiotic prophylaxis, and bundle strategies. Recommendations were often not consistent with evidence, and most were based on low-level studies. CONCLUSION: CPGs did not adhere well to AGREE II reporting standards. Furthermore, there was limited transparency in moving from evidence to recommendations. CDI prevention CPGs need to better adhere to AGREE-II and be transparent in moving from evidence to recommendations, and recommendations need to be consistent with available evidence. Infect Control Hosp Epidemiol 2016;37:901–908